Capsular Management in Hip Arthroscopy: An Anatomic, Biomechanical, and Technical Review - Benjamin D. Kuhns; Alexander E Weber; David M Levy; Asheesh eBedi; Richard C Mather; Michael J Salata; Shane J Nho (Frontiers in Surgery, 2016)
Hip arthroscopy has become an increasingly utilized surgical technique for the treatment of the young, active patient with hip pain. The clinical outcomes of hip arthroscopy in this patient population have been largely successful; however, there is increasing interest in the contribution of hip capsule in postoperative clinical and functional outcomes. The structure and function of the normal hip capsule will be reviewed. Capsular contributions to hip stability will be discussed in the setting of hip arthroscopy with an emphasis on diagnosis-based considerations. Lastly, clinical outcomes following hip arthroscopy will be discussed as they relate to capsular management.